The Intellectual Social History of Islamic Education: The Thoughts of Muslim Intellectuals in the Field of Islamic Religious Sciences - Romadhon Romadhon; Hasan Asari (Sustainable, 2023)
The Islamic Intellectual Tradition developed through three periods: classical times, medieval times, and modern times. These three epochs had different characteristics and methods for developing the Islamic intellectual tradition. However, the classical age had a strong influence on the development of the Islamic intellectual tradition in later times. This paper is put forward as an effort to provide a proper understanding and meaning of how Islam becomes an inseparable part of the intellectual development of Muslims, better known as the Islamic intellectual tradition. This paper attempts to elaborate and show that Islam has an important role in building an intellectual tradition that began through teaching in Islamic boarding schools. The method put forward in this paper is a descriptive method with an analytical approach. Classical times it contributed to intellectual development by placing the methods that developed in teaching and education that were practiced from the time of the Holy Prophetsa, namely the method of writing and memorization. The Middle Ages contributed to the emergence of institutions that aided and developed the Islamic intellectual tradition. Modern times are a struggle of Indonesian Islamic intellectual traditions, which gave birth to two groups of young and old. Young people put forward the importance of renewing thought in the realm of Islamic understanding by methods of returning Islam to its place through understanding Islamic teachings that eliminate the side of taqlid and purify Islamic teachings. The thoughts of Muslim intellectuals in the field of Islam are theology, fiqh, Tafsir, hadith, and akhlaq.